2008
DOI: 10.1111/j.1469-7580.2008.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic right ventricular pressure overload results in a hyperplastic rather than a hypertrophic myocardial response

Abstract: Myocardial hyperplasia is generally considered to occur only during fetal development. However, recent evidence suggests that this type of response may also be triggered by cardiac overload after birth. In congenital heart disease, loading conditions are frequently abnormal, thereby affecting ventricular function. We hypothesized that chronic right ventricular pressure overload imposed on neonatal hearts initiates a hyperplastic response in the right ventricular myocardium. To test this, young lambs (aged 2-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
2
20
1
1
Order By: Relevance
“…The onset, haemodynamic profile and compensatory mechanisms in pulmonary hypertension are very different compared with patients with PV stenosis. In the studied patients, the pressure load is already present to some extent at birth, it is a purely systolic pressure load and neurohormonal or gene and protein synthesis alterations are thought to play a role in the better preservation of right ventricular morphology 19 20 21. To what extent each contributes to this favourable remodelling of the RV has still to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The onset, haemodynamic profile and compensatory mechanisms in pulmonary hypertension are very different compared with patients with PV stenosis. In the studied patients, the pressure load is already present to some extent at birth, it is a purely systolic pressure load and neurohormonal or gene and protein synthesis alterations are thought to play a role in the better preservation of right ventricular morphology 19 20 21. To what extent each contributes to this favourable remodelling of the RV has still to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Occlusion of the LAo likely causes pathological, pressure overload hypertrophy of the right ventricle (Eme et al, 2009a) [see Faber et al (Faber et al, 2006) and Leeuwenburgh et al (Leeuwenburgh, 2008) for mammalian examples], whereas chronic exercise can increase alligator heart mass (Eme et al, 2009b), possibly leading to a greater stroke volume (e.g. Rowell, 1974;Scheuer and Tipton, 1977).…”
Section: Exercise and Lao Occlusion Cause A Synergistic Increase In Vmentioning
confidence: 99%
“…Pulmonary artery banding increases outflow resistance and is a treatment for correction of specific congenital heart defects in humans (Muller and Damman, 1952;Oppido et al, 2004;Locker et al, 2008). Numerous studies have demonstrated that PA banding results in pressure overload hypertrophy of the RV (Faber et al, 2006;Leeuwenburgh et al, 2008). Distinct histological changes are associated with ventricular hypertrophy resulting from different causal mechanisms.…”
Section: Removing Crocodilian R-l Cardiac Shunt Causes Ventricular Enmentioning
confidence: 99%
“…For example, in rats ventricular cellular hypertrophy is associated with a decrease in DNA concentration (Vliegen et al, 1990). By contrast, concomitant increases in both DNA content and ventricular size are indicative of hyperplastic cellular and subcellular 'growth' (Grimm et al, 1970;Linzbach, 1976;Herget et al, 1997;Leeuwenburgh et al, 2008). Hyperplastic growth of the myocardium occurs during normal embryonic and fetal vertebrate development and continues for a short, but indefinite period after hatching or parturition (Li et al, J. Eme and others Mean number of apnoeas Sham Table 2.…”
Section: Removing Crocodilian R-l Cardiac Shunt Causes Ventricular Enmentioning
confidence: 99%